The Oxford handbook of management - Wilkinson, Adrian, 1963-; Armstrong, Steven J.; Lounsbury, Michael (Oxford : Oxford University Press, 2017)
This handbook analyses and explores the evolution of management; the core functions and how they may have changed; its position in the culture of modern society; the institutions and ideologies that support it; and likely challenges and changes in the future.
Introduction / Adrian Wilkinson, Steve Armstrong, Michael Lounsbury -- Managing Operations - production, BPR / Zoe Radnor, Nicola Bateman -- Managing Projects / Jeff Pinto -- Managing Knowledge and Information / Wendy Currie -- Managing Meaning - culture / Violina Rindova -- Management and Leadership / Ronald E. Riggio -- Management and Strategy / Mark Shanley -- Management Practice - and the doing of management / Stefan Tengblad -- Managing Change / David Buchanan -- Scientific Management  / Lucy Taska -- Management as a Practice of Power / David Courpasson -- Evidence Based Management / Kevin Morrell, Mark Learmonth -- Management and Morality/Ethics / Michel Anteby -- Management and Modernity / Graham Sewell -- Management Education and Business Schools  / Ken Brown, Robert S. Rubin -- Management as an Academic Discipline  / Christian De Cock, Damian Doherty -- Managing across Cultures  / Robert Rubin, Stefan Tengblad -- International Management  / Mike Geppert, Graham Hollinshead -- Human Relations  / Kyle Bruce, Chris Nyland -- Management as Consultancy / Andrew Sturdy, Christopher Wright, Nick Wylie -- Operations Management/Systems / Martin Spring -- Management by Objectives  / Peter Starbuck -- Organisational Culture and Image / Mats Alvesson -- Open Systems (contingency theory/design) / Bob Hinings, Roston Greenwood -- Future in the past: a philoshphical reflection on the prospects of management / Stewart Clegg, Marco Berti, Walter P. Jarvis -- Managing People - personnel, HRM, performance / Andy Charlwood, Kim Hoque.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 31, 2017).
Keywords: Management